2021
DOI: 10.1098/rspa.2020.0715
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear viscoelasticity of strain rate type: an overview

Abstract: There are some materials in nature that experience deformations that are not elastic. Viscoelastic materials are some of them. We come across many such materials in our daily lives through a number of interesting applications in engineering, material science and medicine. This article concerns itself with modelling of the nonlinear response of a class of viscoelastic solids. In particular, nonlinear viscoelasticity of strain rate type, which can be described by a constitutive relation for the stress function d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…The sample exhibits strong viscoelasticity in this strain rate range. The modulus and stress increase with strain rate, while fracture strain decreases, similar to common viscoelastic materials. The fracture stress is about 30 MPa, and it weakly depends on the strain rate, which is consistent with previous results. , …”
Section: Resultssupporting
confidence: 89%
“…The sample exhibits strong viscoelasticity in this strain rate range. The modulus and stress increase with strain rate, while fracture strain decreases, similar to common viscoelastic materials. The fracture stress is about 30 MPa, and it weakly depends on the strain rate, which is consistent with previous results. , …”
Section: Resultssupporting
confidence: 89%
“…We provide a brief introduction of the mathematical background covering fundamental equations that form the basis of continuum mechanics, and the formulation of implicit constitutive theory. Similar reviews can also be found in [2,10,14,15].…”
Section: Derivation Of the Modelmentioning
confidence: 59%
“…The dependence of material moduli on the density leads to nonlinear models even in the small strain range, and the impact of this nonlinearity on the solution of the classical boundary value problems of elastic solids must be carefully assessed. (The same holds also for inelastic materials with nonlinearities in the small strain range, see, for example, Rajagopal [22], Bulíček et al [23], or Şengül [24,25] for some studies in this direction. See also Rajagopal and Wineman [26] for a study regarding a viscoelastic solid with density-dependent material moduli.)…”
Section: Discussionmentioning
confidence: 77%